(untitled) (Journal of Educational Sciences, 2017)
The article presents a different vision of the concept of “research culture”, gives the characteristics of this phenomenon in terms of pedagogy, especially description functions of components of the phenomenon; considers a range of research skills as the basis of a research culture. Special attention is paid to the intellectual component of the research culture. The authors introduce the concept of the intellectual and creative research environment of the University as a system contributing to the formation and development of intellectual potential of the participants of the educational process. Signs of environment: motivation research, the saturation of the environment, the organization of the conditions of intellectual activity, positive psychological climate, value and promote the development of intellectual potential. It carried out an empirical study aimed to determine the pedagogical conditions of development of students’ intelligence in the framework of a research culture.